Sociedad de la información y globalización cosmopolita - Reyes, Román (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
Beyond the modernity, once accepting its inherited contradictions, in the XXI century, we will meet a challenge: Looking foreword. Due to recent sayings of Eric Hobsbawn: To relax an ambience using logic and the common sense While keeping a firm compromise for the sake of a government for people (for all kind of the people, rich or poor, stupid or intelligent, informed or ignorant) considering their opinion and consent. Looking foreword is a complicated task, as complicated as the intellectuals and politicians given promise. Yes that’s true, these people has determined to solve the current problems of our time: How to get along with these conflicts and reaching the peace avoiding armed intervention. Instead of preventive war one must have thought of more balanced preventive ways .However, it’s impossible to solve this dilemma before having solved the problems (more real and more theoretical ones) which are justified by a mythical-theoretical rule of nationalism or beyond their notable validity by the perpetual of the mass-media managers.